Wastewater Treatment Works: A Last Line of Defense for Preventing Antibiotic Resistance Entry Into the Environment - Tucker, Keira; Stone, Wendy; Botes, Marelize; Feil, Edward J.; Wolfaardt, Gideon M. (Frontiers in Water, 2022)
With their large, diverse microbial communities chronically exposed to sub-inhibitory antibiotic concentrations, wastewater treatment works (WWTW) have been deemed hotspots for the emergence and dissemination of antimicrobial resistance (AMR), with growing concern about the transmission of antibiotic resistant genes (ARG) and antibiotic resistance bacteria (ARB) into receiving surface waters. This study explored (1) the prevalence of ARG and ARB in local WWTW, (2) the effect of sub-inhibitory antimicrobial exposure on ARG copy numbers in pure cultures from WWTW, and (3) two WWTW with different treatment configurations. For each WWTW, qPCR determined the prevalence of mcr3, sul1, sul2 and blaKPC during the treatment process, and culture methods were used to enumerate and identify ARB. Bacterial colonies isolated from effluent samples were identified by 16S rDNA sequencing and their respective minimum inhibitory concentrations (MIC) were determined. These were compared to the MICs of whole community samples from the influent, return activated sludge and effluent of each WWTW. Resistance genes were quantified in 11 isolated cultures before and after exposure to sub-MIC concentrations of target antibiotics. The numbers of ARG and ARB in both WWTW effluents were notably reduced compared to the influent. Sul1 and sul2 gene copies increased in cultures enriched in sub-MIC concentrations of sulfamethoxazole, while blaKPC decreased after exposure to amoxicillin. It was concluded, within the parameters of this study, that WWTW assist in reducing ARG and ARB, but that sub-inhibitory exposure to antimicrobials has a varied effect on ARG copy number in pure cultures.